Item Response Theory Analysis of Two Questionnaire Measures of Arthritis-Related Self-Efficacy Beliefs from Community-Based US Samples. (13th April 2010) - Mielenz, Thelma J.; Edwards, Michael C.; Callahan, Leigh F.
Abstract : Using item response theory (IRT), we examined the Rheumatoid Arthritis Self-efficacy scale (RASE) collected from a People with Arthritis Can Exercise RCT (346 participants) and 2 subscales of the Arthritis Self-efficacy scale (ASE) collected from an Active Living Every Day (ALED) RCT (354 participants) to determine which one better identifies low arthritis self-efficacy in community-based adults with arthritis. The item parameters were estimated in Multilog using the graded response model. The 2 ASE subscales are adequately explained by one factor. There was evidence for 2 locally dependent item pairs; two items from these pairs were removed when we reran the model. The exploratory factor analysis results for RASE showed a multifactor solution which led to a 9-factor solution. In order to perform IRT analysis, one item from each of the 9 subfactors was selected. Both scales were effective at measuring a range of arthritis SE.